The late nineteenth-century North American catholic schools question tangled disputes over catholic public education in Manitoba and Minnesota - Shanahan, Brendan A. (2024)
Debates over the role of the state in Catholic education rocked both the United States and Canada during the early-to-mid 1890s. Arguably the two most famous of these disputes—the “Manitoba Schools Question” (1890–1897) and the “Faribault Plan” (1890–1893) in Minnesota—unfolded alongside one another in neighboring polities. Both centered on whether Catholic schools could receive taxpayer funding and whether they should be recognized as public institutions. This article explores cross-border press coverage of them to demonstrate their deep top-down and bottom-up ties. It argues they represent two sides of a broader, intertwined late nineteenth-century North American Catholic Schools Question.
Keywords: Catholic Education; United States; Canada; American Protective Association; Faribault Plan; Manitoba Schools Question